The Forgotten (Invisible) Healthcare Heroes: Experiences of Canadian Medical Laboratory Employees Working During the Pandemic - Gohar, Basem; Nowrouzi-Kia, Behdin (Frontiers in Psychiatry, 2022)
Objective: The purpose of this qualitative study was to understand the stressors and coping strategies of medical laboratory technologists (MLTs) and assistants (MLAs) working during the COVID-19 pandemic in Ontario, Canada. Methods: In this descriptive qualitative study, we held two focus groups with MLTs and MLA who were working during the COVID-19 pandemic. The focus group sessions were transcribed verbatim followed by thematic analysis to develop codes and themes. Findings: A total of 13 participants across Ontario were involved in our study, which included one MLT (n=7) group and one MLA (n=6) MLA. Overall, the stressors and coping methods identified between both focus groups were consistent. Our results revealed four main themes:1) COVID-19 contributing to the notable and existing staff shortage; 2) the pandemic reinforced how forgotten medical laboratory employees within the system; 3) a poor work environment exacerbated by the pandemic; and 4) a resilient and passionate group. Rich descriptions explained the underlying issues related to the themes. Conclusions: MLT and MLA are critical members of the healthcare team and provide vital patient care services. This study explored their experiences working during the pandemic and offers timely recommendations to mitigate against occupational stressors.